RESOLUSI KONFLIK PEMILIHAN KEPALA DAERAH DI KECAMATAN TALAGA RAYA KABUPATEN BUTON TENGAH - Mahrudin Mahrudin (Lembaga penelitian dan Pengembangan Masyarakat (LPPM) IAIN Kediri, 2019)
The purpose of this paper is to examine and identify the problems that are the source of conflict over local elections in Talaga Raya District. This research focuses on conflicts that occur before and after local elections. By using a descriptive method and a case study approach, the results of the study showed that the conflict over the regional head election in Talaga Raya District originated from the Difference in Choice, Misunderstanding, Some Parties were disadvantaged and feeling sensitive. In addition, the conflict of local election which took place before and after the election had implications for the conflict over the control of fresh water sources which resulted in horizontal and vertical conflicts. Besides this conflict has also brought its own wisdom with the increase in the source of clean water which had only been one to three sources. Based on these results it can be said that besides bringing down the negative impacts of the conflict it can also bring down positive impacts in the Talaga Raya sub-district community. Therefore, in terms of conflict resolution, the government should be able to minimize the conflict as early as possible so it does not drag on so that it does not lead to physical conflict.